Design and fabrication of drug‐eluting polymeric thin films for applications in ophthalmology. Issue 8 (29th August 2018) - Lamprogiannis, Lampros; Karamitsos, Athanasios; Karagkiozaki, Varvara; Tsinopoulos, Ioannis; Gioti, Maria; Fatouros, Dimitrios G.; Dimitrakos, Stavros; Logothetidis, Stergios
Abstract : To study the development, characterisation, and drug release of one‐ and two‐layered thin films based on organic polymers [poly(D, L‐lactide‐ co ‐glycolide) lactide:glycolide (65:35), poly(D, L‐lactide‐ co ‐glycolide) lactide:glycolide (75:25), and polycaprolactone] and dexamethasone. To examine their applicability for intraocular lenses (IOLs) and function in intraocular drug delivery systems. Four series of thin films, single and double‐layer, were prepared by the spin‐coating method on a silicon substrate. The films were studied using atomic force microscopy and spectroscopic ellipsometry. The release rate of dexamethasone was studied for a period of ten weeks. Series A and C demonstrated the formation of large dexamethasone aggregates. The monolayer films of series C and D formed pores, in agreement with previous findings. The spectroscopic ellipsometry study demonstrated that the samples were transparent. The drug release study demonstrated that dexamethasone was released during the first 6 weeks at a desirable rate. The films exhibited properties suitable for use in intraocular drug delivery systems. The single‐layer thin films demonstrated a sufficient encapsulation of dexamethasone and appropriate release of the therapeutic substance. Further studies are necessary to investigate the possibility of developing the films directly on the surface of the IOL.